Huoxue Qingre decoction used for treatment of coronary heart disease network analysis and metabolomic evaluation - Tan, Yu-Qing; Jin, Min; He, Xuan-Hui; Chen, Heng-Wen (Frontiers in Pharmacology, 2022)
Network pharmacology provides new methods and references for the research of traditional Chinese medicine, but some problems remain, such as single evaluation components and index methods, imperfect relevant databases, unscientific prediction results, and lack of verification of results. Herein, we used a modified network pharmacology research method to explore the potential network analysis mechanism of Huoxue Qingre decoction in the treatment of coronary heart disease and utilized clinical trials for assessment. Based on literature research, the targets corresponding to the drug were obtained with the assistance of the TCMSP database and Swiss Target Prediction, and the target proteins were corrected using the UniProt database. The targets related to coronary heart disease was obtained through the GeneCards database. A protein-protein interaction network diagram was constructed, and a ‘component-intersection target’ network diagram was drawn based on Cytoscape 3.6.2 software. The mapped targets were imported into the DAVID bioinformatics platform, which underwent Gene Ontology (GO) function and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, and the network pharmacology prediction results were evaluated through clinical trials. We obtained 151 compounds related to Huoxue Qingre decoction, 286 genes after evaluation and deduplication, and 426 genes related to coronary heart disease. Finally, 81 common target genes were obtained with 32 pathways according to the KEGG pathway enrichment analysis. The validation results of the clinical trials showed that a total of 98 differential metabolites were found in the treatment of coronary heart disease with Huoxue Qingre decoction, involving a total of 16 metabolic pathways. Compared with the network pharmacology prediction results, it was found that only the pathways in cancer (hsa05200) were the common pathways in the top 32 signaling pathways predicted by network pharmacology. The expanded network pharmacology prediction results revealed that the sphingolipid signaling pathway (hsa04071) and prostate cancer pathway (hsa05215) matched the predicted metabolic pathways, with differential metabolites of N-oleoyl-D-sphingomyelin and 1-methyl-6-phenyl-1h-imidazole[4,5-b]pyridine-2-amine. Through the network analysis and metabolomic evaluation, there may be three signaling pathways that involve the Huoxue Qingre decoction in the treatment of coronary heart disease: pathways in cancer (hsa05200), sphingolipid signaling pathway (hsa04071), and prostate cancer pathway (hsa05215).